(untitled) (JURNAL IBU DAN ANAK, 2020)
ABSTRACT Antenatal care is very important in reducing mortality due to childbirth. The purpose of this study is to determine the relationship between husband’s motivation and antenatal care visits in the Sipayung Health Center in 2017. The method used is analytical with a sampling technique with a random sampling technique. Research conducted in December 2017 in the Work Area of the Sipayung Puskesmas, Rengat District, Indragiri Hulu Regency, obtained the following results: the husband’s motivation in the ANC visit was positive as many as 73 people (87%) and negative as many as 11 people (13%). Of the 84 people who visited the ANC, 63 people (75%) had complete ANC visits and 21 (25%) were incomplete. The results of the study using bivariate analysis obtained P> 0.005 (P = 0.277). The conclusion of this study is that there is no relationship between husband’s support for antenatal care visits in the Sipayung Health Center Work Area in 2017.